Daturaolone from Datura metel L. Inhibits acetylcholinesterase and monoamine oxidase B - Bilal Khan; Marryum; Abdur Rauf; Ayesha Tahir; Umer Rashid; Hira Naeem; Muhammad Saeed Jan; Muhammad Shafique; Saima Naz; Alessandra Gianoncelli; Giovanni Ribaudo (Natural Product Research, 2026)

Pharmacokinetic evaluation and in vivo anti-inflammatory potential of cyanoacetate derivatives of succinimide - Aini Pervaiz; Muhammad Saeed Jan; Ali Khan; Bushra Ansari; Imad Ahmad; Wadood Ali Shah; Syed Muhammad Mukarram Shah; Abdur Rauf; Abdullah S. M. Aljohani; Waleed Al Abdulmonem; Marcello Iriti (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
The purpose of the study is to evalute the in vivo anti -inflammatory activity of newly synthesized cyanoacetate derivatives of succinimides (C-23, C-31, and C-44) and to elucidate their possible mechanisms of action through key inflammatory mediator pathways. Anti-inflammatory activity was assessed using carrageenan-induced paw oedema and arachidonic acid-induced ear oedema models in vivo. Mechanistic involvement was investigated through histamine-, prostaglandin-, leukotriene-, and bradykinin-induced paw oedema assays. In silico ADME studies were performed to predict pharmacokinetic properties and metabolic interactions. All tested compounds exhibited significant anti-inflammatory activity, with C-44 showing the highest potency. Mechanistic studies indicated that the anti-inflammatory effects were predominantly mediated via inhibition of prostaglandin and leukotriene pathways. ADME predictions suggested high gastrointestinal absorption, favourable oral bioavailability, and minimal interaction with major metabolic enzymes. The synthesized cyanoacetate derivatives, particularly C-44, demonstrate promising anti-inflammatory potential with favourable pharmacokinetic profiles, supporting their candidacy for further development as effective anti-inflammatory agents.

Inter-device interaction effects on turbine performance and blade loads in axially aligned tidal turbine arrays - Mujahid Badshah; Saeed Badshah; Sajjad Ahmad; Imtiaz Alam Shah; Zia Ur Rehman; Muhammad Amjad; Sakhi Jan (Ocean Engineering, 2026)

Influence of inter-device spacing on performance and blade loads in staggered arrays of tidal current turbines - Mujahid Badshah; Saeed Badshah; Zia Ur Rehman; Sajjad Ahmad; Muhammad Amjad; Sakhi Jan; Imtiaz Alam Shah (Ocean Engineering, 2026)

Microplastics as Trojan horses: Vectors of pathogens, pollutants, and antimicrobial resistance genes - Ghazala Saeed; Ali Afzal; Afzal Nimra; Zaira Ahmad; Amna Rehman; Kaleem Maqsood; Tayyba Jan; Muhammad Ishfaq Ahmad; Naveed Karim; Byong-Hun Jeon; Ghulam Mustafa; Fakhar Zaman; et al. (Environmental Research, 2026)

Comprehensive in-vitro study of anticholinesterase, anti-inflammatory, and antidiabetic properties of congress grass (Parthenium hysterophorus) methanolic extract - Abdur Rauf; Muhammad Ibrahim; Yahya S. Al-Awthan; Omar S. Bahattab; Hassan A. Hemeg; Anees Ahmed Khalil; Ahood Khalid; Samiah Shahid; Hina Gull; Muhammad Saeed Jan; Dorota Formanowicz; Marcello Iriti (Plant Biosystems, 2026)

Beyond limitations: Integrating advanced analytical techniques for a new era of soil organic matter characterization - Adnan MUSTAFA; Qudsia SAEED; Lasisi H. TOBILOBA; Yakov KUZYAKOV; Muhammad NAVEED; Mohammad T.K. NEZHAD; Muhammed M. IBRAHIM; Jan FROUZ; Martin BRTNICKY; Jiri KUCERIK; Xiankai LU (Pedosphere, 2026)

The green supply chain conundrum: exploring the interplay of practices, performance, and technology in shaping SME sustainability in developing country - Ikramuddin Junejo; Jan Muhammad Sohu; Aiza Aziz Qureshi; Saba Shaikh; Faisal Ejaz; Tahir Saeed Jagirani; Md Billal Hossain (Environment, Development and Sustainability, 2025)

In-vitro, in-vivo and computational experiments for the antidiabetic potential of bioactive compound from Notholirion thomsonianum - Abdulaziz Hassan Alhasaniah; Abdul Sadiq; Ahmed Abdullah Al Awadh; Yahya I. Asiri; Meriem Rezigue; Rehman Zafar; Sajjad Ahmad; Muhammad Saeed Jan; Mater H. Mahnashi (Natural Product Research, 2025)

Cenchrus ciliaris L. ameliorates cigarette-smoke induced acute lung injury by reducing inflammation and oxidative stress - Muhammad Irfan Aslam; Saad Touqeer; QurratUlAin Jamil; Muhammad Irfan Masood; Adeel Sarfraz; Shafaat Yar Khan; Muhammad Saeed Jan; Sulaiman Mohammed Abdullah Alnasser; Ashfaq Ahmad; Fatima Aslam; Shahid Muhammad Iqbal (South African Journal of Botany, 2024)

Enhancing wheat performance through phosphorus and zinc management strategies under varied irrigation regimes - Abdul Latif Jan; Amanullah; Adil Mihoub; Muhammad Fawad; Muhammad Farhan Saeed; Imad Khan; Emanuele Radicetti; Aftab Jamal (Environment, Development and Sustainability, 2024)

Isolation, invitro, invivo anti-inflammatory, analgesic and antioxidant potential of Habenaria plantegania Lindl - Osama M. Alshehri; Madeeha Shabnam; Saeed Ahmed Asiri; Mater H. Mahnashi; Abdul Sadiq; Muhammad Saeed Jan (Inflammopharmacology, 2024)

2-Hydroxybenzohydrazide as a novel potential candidate against nociception, inflammation, and pyrexia: in vitro, in vivo, and computational approaches - Gowhar Ali; Nazar Ul Islam; Muhammad Qaim; Rahim Ullah; Muhammad Saeed Jan; Khadija Shabbiri; Muhammad Shafique; Muhammad Ayaz (Inflammopharmacology, 2024)

A review of gas chromatographic techniques for identification of aqueous amine degradation products in carbonated environments - Idris Mohamed Saeed; Shaukat Ali Mazari; Peter Alaba; Brahim Si Ali; Badrul Mohamed Jan; Wan Jeffrey Basirun; Yahaya Muhammad Sani; Sabzoi Nizzamuddin; Nabisab Mujawar Mubarak (Environmental Science and Pollution Research, 2021)

Assessment of subsurface lithology, groundwater depth, and quality of UET Lahore, Pakistan, using electrical resistivity method - Zahid Mehmood; Noor Muhammad Khan; Shamsher Sadiq; Saeed-ullah Jan Mandokhail; Syed Zishan Ashiq (Arabian Journal of Geosciences, 2020)

Biological Activities of Artemisinins Beyond Anti-Malarial: a Review - Saeed-ur-Rahman; Muhammad Khalid; Sadaf-Ilyas Kayani; Farooq Jan; Ayaz Ullah; Kexuan Tang (Tropical Plant Biology, 2019)

Knockdown of the chitin-binding protein family gene CaChiIV1 increased sensitivity to Phytophthora capsici and drought stress in pepper plants - Muhammad Ali; Wen-Xian Gai; Abdul Mateen Khattak; Abid Khan; Saeed Ul Haq; Xiao Ma; Ai-Min Wei; Izhar Muhammad; Ibadullah Jan; Zhen-Hui Gong (Molecular Genetics and Genomics, 2019)